A detailed theoretical exploration on the THR-β binding affinities and antioxidant activity of some halogenated bisphenols. Issue 21 (5th December 2022) - Gheshlaghi, Saman Zare; Ebrahimi, Ali; Faghih, Zeinab
Abstract: Natural halogenated phenolic compounds are unique bioactive structures which share features and physicochemical properties with thyroid hormones, who are essential regulators of neurological development and metabolism processes. Also, these structures can be used as natural antioxidants to minimize the diseases related to oxidative stress. In this work, the binding affinity of 32 natural and synthetic halogenated bisphenols were investigated on thyroid hormone receptor-β (THR-β) using the molecular docking, MM/GBSA, molecular dynamics, and a rigorous three-layer ONIOM ((M06-2X/6-31G*:PM6:AMBER) calculation. The desirable potency is observed for binding of selected compounds to THR-β. The Met313, Asn331, and His435 are the main interacting residues in the binding cavity which involved in the hydrogen and halogen bond interactions with the ligands. The most potent candidate on binding to the active site of THR-β is presented with respect to the results of mentioned calculations. Moreover, the antioxidant activity of compounds has been investigated using the quantum mechanical calculations. The electrostatic potential surfaces illustrate well the antioxidant capacity of compounds. The halogen substituents increase the antioxidant activity of the most stable conformers. The position and number of OH groups are crucial factors which affect the activity, whereas two adjacent hydroxyl groups enhance the antioxidant activity of selected compounds. Communicated by Ramaswamy H. Sarma